The influential factors on the diffusion of smartwatches in Korea. (2016) - Cho, Insu; Park, Heejun
This study investigates the characteristics of smartwatches and examines the important variables pertaining to the adoption of smartwatches by consumers. Based on previous research and interviews, this study sets emotional design, content quality, and system quality as external factors. In the perception layer with regard to directly influences of the intention to use smartwatches, this study sets performance expectancy, effort expectancy, hedonic motivation, social influence, and price value based on the extended unified theory of acceptance and use of technology (UTAUT2). Based on 273 samples in the Republic of Korea, this study empirically tests the research model using a structural equation model. The findings imply several implications which can be used to bolster the intention to use smartwatches. Moreover, practitioners can establish the future development directions of smartwatches.